Formuła efektywnego przedsiębiorstwa uwzględniająca jego oddziaływanie na środowisko - Różański, Jerzy (Formula of an Effective Enterprise Taking its Impact on the Environment into Account, 2006)
A modern enterprise, functioning within market economy, should take the effects which its activity has on the natural environment into account. The full economic calculation made by such an enterprise must include not only the costs incurred by it in connection with the requirements of environmental protection, but also the total costs incurred by the enterprise itself and by its surroundings in relation to production and services provided by such a given enterprise. The paper presents proposals of including the effects that an enterprise has on its surroundings in the cost calculation of expenditures incurred by the enterprise as well as in the evaluation of stability of its functioning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 528-533